1993
DOI: 10.1128/jcm.31.11.2873-2877.1993
|View full text |Cite
|
Sign up to set email alerts
|

Genomic fingerprinting of Borrelia burgdorferi sensu lato by pulsed-field gel electrophoresis

Abstract: A total of 46 Borrelia burgdorferi sensu lato isolates that were isolated from patients with Lyme borreliosis and infected animals or were extracted from ticks of the genus lxodes were analyzed. Large restriction fragment patterns obtained after cleavage of genomic DNAs with Mlul were analyzed by pulsed-field gel electrophoresis (PFGE). To eliminate the contribution of plasmid DNA, only frmMents greater than 70 kb were used for the analysis. The results indicated that each of the 14 B. burgdorferi sensu strict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 28 publications
2
46
1
Order By: Relevance
“…Earlier studies on PFGE analysis of the Borrelia genome demonstrated their usefulness in identifying isolates, and a species identified by PFGE exactly corresponded to that obtained previously with other methods (6). We used PFGE analysis to identify several Japanese borrelial isolates and the results are presented in this paper.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Earlier studies on PFGE analysis of the Borrelia genome demonstrated their usefulness in identifying isolates, and a species identified by PFGE exactly corresponded to that obtained previously with other methods (6). We used PFGE analysis to identify several Japanese borrelial isolates and the results are presented in this paper.…”
supporting
confidence: 59%
“…Pulsed field gel electrophoresis ( PFGE) is a newly developed tool for characterizing large restriction fragments produced by rare-cutter restriction enzymes. Earlier studies revealed that this method was successfully used to construct a physical map of the B. burgdorferi genome and is also useful in identifying geographical isolates as belonging to a specific species and for epidemiological studies (5,6). We analyzed several B. burgdorferi sensu lato isolates by PFGE.…”
mentioning
confidence: 99%
“…Genomic fingerprinting of B. burgdorferi sensu lato strains by pulsed-field gel electrophoresis (PFGE) showed that all isolates used in this study were recognized by one band (135 kbp), each of the B. garinii isolates by two bands (220 and 80 kbp), and each of the B. afzelii isolates by three bands (460, 320 and 90 kbp). Whilst there were differences in the PFGE patterns among B. burgdorferi and B. garinii isolates, the patterns of B. afzelii isolates were all similar [15]. The number of genomic species was further expanded by the characterization of borreliae isolated from Ixodes ovatus ticks in Japan.…”
Section: Expansion Of the Lyme Borrelia Complex During The 1990smentioning
confidence: 99%
“…Lyme borreliosis, the most common tick-borne infection in the Northern hemisphere, is caused by the spirochete Borrelia burgdorferi sensu lato (1). At least three species have been associated with human Lyme borreliosis: B. afzelii, B. garinii and B. burgdorferi sensu stricto (2). The disease manifestations and the outcome seem to depend at least partly on the nature of the infecting organism (3,4).…”
mentioning
confidence: 99%